2022
DOI: 10.3390/su15010044
|View full text |Cite
|
Sign up to set email alerts
|

Green Lifestyle: A Tie between Green Human Resource Management Practices and Green Organizational Citizenship Behavior

Abstract: Increasingly negative business processes and climate change have prompted businesses to incorporate green lifestyle practices into their working systems as a promising first step. This study investigates the impact of green human resource management practices on green organizational citizenship behavior, with a green lifestyle acting as a mediator and green innovation and green shared value acting as moderators. The data were collected from 347 hotel industry employees in China, and the partial least squares s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 66 publications
(155 reference statements)
0
23
0
3
Order By: Relevance
“…Additionally, employee commitment plays a mediating role in the relationship between Green HRM practices and sustainable firm performance (DIN, 2023). Furthermore, the research has demonstrated that a green lifestyle positively mediates the relationship between Green HRM practices and green organizational citizenship behavior (Meng et al, 2022).…”
Section: The Relationship Between Employee Involvement In Green Hrm P...mentioning
confidence: 98%
“…Additionally, employee commitment plays a mediating role in the relationship between Green HRM practices and sustainable firm performance (DIN, 2023). Furthermore, the research has demonstrated that a green lifestyle positively mediates the relationship between Green HRM practices and green organizational citizenship behavior (Meng et al, 2022).…”
Section: The Relationship Between Employee Involvement In Green Hrm P...mentioning
confidence: 98%
“…Such training not only facilitates the acquisition of essential green skills but also fosters an understanding of the significance of employees' contributions to the organization's sustainability and well-being objectives (Nasir et al, 2023b). Performance appraisal within the framework of Green Human Resource Practices (GHRP) integrates both environmentally conscious behaviors and employees' adherence to wellness practices into the criteria used for evaluating performance (Meng et al, 2023). Recognizing and rewarding employees' efforts to minimize their environmental impact, engage in eco-friendly practices, or suggest improvements to augment sustainability alongside their commitment to maintaining personal well-being sends a clear message: the organization values environmental responsibility and employee health equally.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green Human Resource Practices denote the strategies and actions taken by organizations to promote a sustainable and environmentally responsible work environment. Recognizing the importance of sustainability and a reduced ecological footprint, GHRP aims to intertwine ecological consciousness with standard HR activities (Meng et al, 2023). Several pivotal initiatives fall under the umbrella of GHRP:…”
Section: Green Human Resource Practices (Ghrp)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because creative solutions for going green stem from specific traits within people and organizations, creating a ripple effect of positive impact (Tuan, 2023). A multitude of factors contribute to green creativity, including the organizational commitment to environmental practices, a culture of eco-innovation, employees' green lifestyle, and green transformational leadership (Öğretmenoğlu et al, 2022;Meng et al, 2022;Tuan, 2023). Environmental and social progress hinges on a potent combination of novel ideas and their subsequent translation into action (Singh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%